Rare and common variants in ERAP1 and ERAP2 selected for in response to Yersinia pestis infection contribute to autoimmune disease including inflammatory bowel disease - Lynn K. Win; Guo Cheng; James J. Ashton; Alex Z. Kadhim; Zachary Green; R. Mark Beattie; Sarah Ennis (Mammalian Genome, 2026)
Endoplasmic reticulum aminopeptidases (ERAP) facilitate antigen presentation. Variation in ERAP1 and ERAP2 genes underwent selection during the Black Death and impact autoimmune disease susceptibility. We assess the burden of functionally impactful variants present in ERAP1 and ERAP2 in 2 cohorts of patients diagnosed with inflammatory bowel disease (IBD; Crohn’s disease (CD) or ulcerative colitis (UC)). We analysed the Southampton Genetics of IBD cohort comprising patients diagnosed with IBD, with exome and clinical data on autoimmune comorbidities (n CD = 661, n UC = 330); and a subset of UK Biobank IBD patients and selected controls (n CD = 891, n UC = 1409, n control = 60,075). Common single variants (minor-allele-frequency > 0.05) underwent Fisher’s exact test with permutations (n = 1000), comparing UC versus CD patients in the Southampton cohort. A gene-burden based test of functionally impactful variants (GenePy) was used to examine rare and common variants in both cohorts. Predicted haplotypes were assessed in each cohort and compared with known haplotypes of ERAP1 and ERAP2 . In the Southampton cohort, variant-level analysis identified 6 common variants that were nominally significant when testing between UC versus CD ( p < 0.05; empirical permuted p-value). Gene-level analysis using Mann–Whitney-U identified an altered burden of functionally impactful variants for ERAP1 in UC versus CD patients ( p = 0.0073), but not for ERAP2 . Patients with an isolated diagnosis of UC ( p = 0.037,θ = 0.457) vs patients with a concurrent diagnosis of UC and any autoimmune diagnoses had an altered burden of functionally impactful variants in ERAP2 . For the UK Biobank cohort, participants diagnosed with UC versus controls had a significantly altered burden of functionally impactful variants in ERAP1 ( p = 0.0004) and ERAP2 ( p = 0.0006). Both variant and gene-level analysis indicate a role for ERAP1 and ERAP2 in predisposing individuals to developing UC or UC with concurrent autoimmune diagnosis.

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Performance of Spectral Indices and Machine Learning Algorithms in Seasonal Classification of Urban Impervious Surfaces from Sentinel-2 Imagery: A Case Study of Taipei - Alex Ssewanyana; Min-Cheng Tu (Remote Sensing in Earth Systems Sciences, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Hydroxyl-driven homogeneous and robust SAM anchoring on NiOx for high-performance inverted perovskite solar cells - Xiao Wu; Haoran Yang; Ziyao Yue; Yunfan Wang; Manting Liu; Jie Zeng; Leyu Bi; Qing-Dan Yang; Yanping Huo; Liming Ding; Alex K.-Y. Jen; Sai-Wing Tsang; et al. (Chemical Engineering Journal, 2025)

Genome-Wide DNA Methylation Profiling Reveals Low Methylation Variability in Moyamoya Disease - Kikutaro Tokairin; Masaki Ito; Alex G. Lee; Mario Teo; Shihao He; Michelle Y. Cheng; Gary K. Steinberg (Translational Stroke Research, 2025)
Moyamoya disease (MMD) is a chronic cerebrovascular disorder that can lead to stroke and neurological dysfunctions. Given the largely sporadic nature and the role of gene-environment interactions in various diseases, we examined epigenetic modifications in MMD. We performed genome-wide DNA methylation using Illumina 850 K Methylation EPIC BeadChip, in two racially distinct adult female cohorts: a non-Asian cohort (13 MMD patients and 7 healthy controls) and an Asian cohort (14 MMD patients and 3 healthy controls). An additional external cohort with both sexes (females: 5 MMD patients and 5 healthy controls, males: 5 MMD patients and 5 healthy controls) was included for validation. Our findings revealed strikingly low DNA methylation variability between MMD patients and healthy controls, in both MMD female cohorts. In the non-Asian cohort, only 6 probes showed increased variability versus 647 probes that showed decreased variability. Similarly, in the Asian cohort, the MMD group also displayed a reduced methylation variability across all 2845 probes. Subsequent analysis showed that these differentially variable probes are located on genes involved in key biological processes such as methylation and transcription, DNA repair, cytoskeletal remodeling, natural killer cell signaling, cellular growth, and migration. These findings mark the first observation of low methylation variability in any disease, contrasting with the high variability observed in other disorders. This reduced methylation variability in MMD may hinder patients’ adaptability to environmental shifts, such as hemodynamic stress, thereby influencing vascular homeostasis and contributing to MMD pathology. These findings offer new insights into the mechanisms of MMD and potential treatment strategies.

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Inverting continuous in-tunnel passive seismic data for velocity structure mapping ahead of the TBM cutterhead - Enhedelihai Alex Nilot; Yunyue Elita Li; Gang Fang; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

Correction to: Comprehensive Profiling of Secreted Factors in the Cerebrospinal Fluid of Moyamoya Disease Patients - Kumar Abhinav; Alex G. Lee; Arjun V. Pendharkar; Mark Bigder; Anthony Bet; Yael Rosenberg-Hasson; Michelle Y. Cheng; Gary K. Steinberg (Translational Stroke Research, 2024)

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Quantifying tunneling risks ahead of TBM using Bayesian inference on continuous seismic data - Gang Fang; Enhedelihai Alex Nilot; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2024)

A state-of-the-science review of using mitochondrial DNA copy number as a biomarker for environmental exposure - Qing Cheng; Qing Qing Liu; Chensheng (Alex) Lu (Environmental Pollution, 2024)

Comprehensive Profiling of Secreted Factors in the Cerebrospinal Fluid of Moyamoya Disease Patients - Kumar Abhinav; Alex G. Lee; Arjun V. Pendharkar; Mark Bigder; Anthony Bet; Yael Rosenberg-Hasson; Michelle Y. Cheng; Gary K. Steinberg (Translational Stroke Research, 2024)
Moyamoya disease (MMD) is characterized by progressive occlusion of the intracranial internal carotid arteries, leading to ischemic and hemorrhagic events. Significant clinical differences exist between ischemic and hemorrhagic MMD. To understand the molecular profiles in the cerebrospinal fluid (CSF) of MMD patients, we investigated 62 secreted factors in both MMD subtypes (ischemic and hemorrhagic) and examined their relationship with preoperative perfusion status, the extent of postoperative angiographic revascularization, and functional outcomes. Intraoperative CSF was collected from 32 control and 71 MMD patients (37 ischemic and 34 hemorrhagic). Multiplex Luminex assay analysis showed that 41 molecules were significantly elevated in both MMD subtypes when compared to controls, including platelet-derived growth factor-BB (PDGF-BB), plasminogen activator inhibitor 1 (PAI-1), and intercellular adhesion molecule 1 (ICAM1) ( p < 0.001). Many of these secreted proteins have not been previously reported in MMD, including interleukins (IL-2, IL-4, IL-5, IL-7, IL-8, IL-9, IL-17, IL-18, IL-22, and IL-23) and C-X-C motif chemokines (CXCL1 and CXCL9). Pathway analysis indicated that both MMD subtypes exhibited similar cellular/molecular functions and pathways, including cellular activation, migration, and inflammatory response. While neuroinflammation and dendritic cell pathways were activated in MMD patients, lipid signaling pathways involving nuclear receptors, peroxisome proliferator-activated receptor (PPAR), and liver X receptors (LXR)/retinoid X receptors (RXR) signaling were inhibited. IL-13 and IL-2 were negatively correlated with preoperative cerebral perfusion status, while 7 factors were positively correlated with the extent of postoperative revascularization. These elevated cytokines, chemokines, and growth factors in CSF may contribute to the pathogenesis of MMD and represent potential future therapeutic targets.

Outcome-Based blind tests for leakage diagnosis in underground watermains by acoustic technologies - Wallace Wai-Lok Lai; Tom Chun-Wai Lau; Alex Yu-Ching Cheng; Panda Kai-Chun Liu; Joseph Wang-Chi Leung (Tunnelling and Underground Space Technology, 2023)

Real-time tunneling risk forecasting using vibrations from the working TBM - Enhedelihai Alex Nilot; Gang Fang; Yunyue Elita Li; Yun Zhou Tan; Arthur Cheng (Tunnelling and Underground Space Technology, 2023)

Championing inclusive terminology in ecology and evolution - Susan J. Cheng; Kaitlyn M. Gaynor; Alex C. Moore; Kathy Darragh; Cesar O. Estien; J.W. Hammond; Christopher Lawrence; Kirby L. Mills; Marcella D. Baiz; Danielle Ignace; Lily Khadempour; Matthew A. McCary; et al. (Trends in Ecology & Evolution, 2023)

Centenarian clocks: epigenetic clocks for validating claims of exceptional longevity - Eric Dec; James Clement; Kaiyang Cheng; George M. Church; Michael B. Fossel; David H. Rehkopf; Luis Rosero-Bixby; Michael S. Kobor; David TS. Lin; Ake T. Lu; Zhe Fei; Wei Guo; et al. (GeroScience, 2023)
Claims surrounding exceptional longevity are sometimes disputed or dismissed for lack of credible evidence. Here, we present three DNA methylation-based age estimators (epigenetic clocks) for verifying age claims of centenarians. The three centenarian clocks were developed based on n = 7039 blood and saliva samples from individuals older than 40, including n = 184 samples from centenarians, 122 samples from semi-supercentenarians (aged 105 +), and 25 samples from supercentenarians (aged 110 +). The oldest individual was 115 years old. Our most accurate centenarian clock resulted from applying a neural network model to a training set composed of individuals older than 40. An epigenome-wide association study of age in different age groups revealed that age effects in young individuals (age < 40) are correlated ( r = 0.55) with age effects in old individuals (age > 90). We present a chromatin state analysis of age effects in centenarians. The centenarian clocks are expected to be useful for validating claims surrounding exceptional old age.

Large‐scale reforestation can increase water yield and reduce drought risk for water‐insecure regions in the Asia‐Pacific - Hoong Chen Teo; Srivatsan V. Raghavan; Xiaogang He; Zhenzhong Zeng; Yanyan Cheng; Xiangzhong Luo; Alex M. Lechner; Matthew J. Ashfold; Aakash Lamba; Rachakonda Sreekar; Qiming Zheng; Anping Chen; et al. (Global Change Biology, 2022)
Large‐scale reforestation can potentially bring both benefits and risks to the water cycle, which needs to be better quantified under future climates to inform reforestation decisions. We identified 477 water‐insecure basins worldwide accounting for 44.6% (380.2 Mha) of the global reforestation potential. As many of these basins are in the Asia‐Pacific, we used regional coupled land‐climate modeling for the period 2041–2070 to reveal that reforestation increases evapotranspiration and precipitation for most water‐insecure regions over the Asia‐Pacific. This resulted in a statistically significant increase in water yield ( p

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Satellite characterization of drought over cultivated areas in Central America - Nguyen-Thanh Son; Chi-Farn Chen; Cheng-Ru Chen; Alex Castellón; Mario-Giovanni- Molina Masferrer; Luis-Eduardo-Menjívar Recinos (International Journal of Remote Sensing, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

In vitro propagation of four threatened Paphiopedilum species (Orchidaceae) - Bo Long; Alex X. Niemiera; Zhi-ying Cheng; Chun-lin Long (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)